Mathematics with the Flipped Classroom: an experience with edpuzzle (Revista BOEM, 2024)
This article is presented as part of a research that focuses on the influence of active methodologies, namely the flipped classroom, on mathematics teaching and learning. Thus, this reports an experience with the use of video on the edpuzzle platform, in the aforementioned curricular component, with the objective of verifying the efficiency resulting from the use of active methodologies applied in the delivery of mathematical content. Regarding methodological aspects, descriptive and comparative longitudinal research was adopted, with a mixed approach, carried out in the form of action research, which made it possible to study a social situation with the objective of improving the quality of the action developed within it. As research participants, we had 35(thirty-five) students and 4 (four) mathematics teachers from Erem Fábio da Silveira Barros. In order to obtain answers to the questions addressed, we used the questionnaire for students, interviews for teachers, participant observation and document analysis as instruments for data collection. Thus, it was noticed that the results of this investigation showed significant contributions of this methodology to the teaching of mathematics. In this way, the research allowed students to take a different look at mathematical learning, providing interaction between content and reality and being the protagonist of meaningful learning.